Co-determination in Germany - a beginners' guide. 5. überarbeitete Auflage - Rebecca Page (Hans-Böckler-Stiftung, 2011)
'The word 'co-determination', or 'Mitbestimmung' in German, is commonly heard outside of Germany but it's actual meaning is often unclear.This collection of texts aims to provide a basic explanation of what co-determination is all about, how it functions in practice and what it means to the Germans and to Germany as whole. The relationship between the German co-determination system and developments within Europe are also considered.'
Keywords: 330